Flow modeling and simulation for vacuum assisted resin transfer molding process with the equivalent permeability method - Chen, R.; Dong, Chensong; Liang, Z.; Zhang, C.; Wang, B. (Wiley Interscience, 2004)
Vacuum assisted resin transfer molding (VARTM) offers numerous advantages over traditional resin transfer molding, such as lower tooling costs, shorter mold filling time and better scalability for large structures. In the VARTM process, complete filling of the mold with adequate wet-out of the fibrous preform has a critical impact on the process efficiency and product quality. Simulation is a powerful tool for understanding the resin flow in the VARTM process. However, conventional three-dimensional Control Volume/Finite Element Method (CV/FEM) based simulation models often require extensive computations, and their application to process modeling of large part fabrication is limited. This paper introduces a new approach to model the flow in the VARTM process based on the concept of equivalent permeability to significantly reduce computation time for VARTM flow simulation of large parts. The equivalent permeability model of high permeable medium (HPM)proposed in the study can significantly increase convergence efficiency of simulationby properly adjusting the aspect ratio of HPM elements. The equivalent permeability model of flow channel can simplify the computational model of the CV/FEM simulation for VARTM processes. This new modeling technique was validated by the results from conventional 3D computational methods and experiments. The model was further validated with a case study of an automobile hood component fabrication. The flow simulation results of the equivalent permeability models were in agreement with those from experiments. The results indicate that the computational time required by this new approach was greatly reduced compared to that by the conventional 3D CV/FEM simulation model, while maintaining the accuracy of filling time and flow pattern. This approach makes the flow simulation of large VARTM parts with 3D CV/FEM method computationally feasible and may help broaden the application base of the process simulation.